PENGARUH WORK LIFE BALANCE DAN PENGEMBANGAN KARIR TERHADAP LOYALITAS PEGAWAI PADA POLITEKNIK BATULICIN - Salsabila Rihhadatul 'Aisy; Taharuddin; Setio utomo; Devi Rusvitawati (Smart Business Journal (SBJ), 2026)
Salsabila Rihhadatul ‘Aisy. 2210412320007. (2026). The Effect of Work Life Balance and Career Development on Employee Loyalty at Politeknik Batulicin. Under the guidance of: Taharuddin. This research aims to determine the effect of Work Life Balance and career development on employee loyalty. The sample in this study consists of all employees at Politeknik Batulicin, The sampling technique used is saturated sampling (census sampling), in which all members of the population are included as respondents. The data collection method employed was a questionnaire, and the data analysis technique used was multiple linear regression. The results indicate that Work Life Balance and career development simultaneously have a significant effect on employee loyalty. Partially, Work Life Balance does not have a significant effect on employee loyalty, while career development has a significant effect on employee loyalty